CONCEPTUALISATION OF SUMBA PEOPLE IN INTERPRETING NUKKU ZARA IN RITUAL SPEECH OF PANGADI NGA'A PABENUDI WE'E MARAPU - Kamuri, Paulus Ama; Mone, Yohanis Rangga (Postgraduate School, Universitas Nusa Cendana, 2024)
The purpose of this research is to identify and describe the cultural practice of conceptualisation of Sumba people in interpreting Nukku Zara in the ritual speech of Pangadi Nga'a Pabenudi We'e Marapu. The research method used is qualitative research with an ethnographic approach. The collection techniques were observation, interview, and document study. Data analysis begins with data reduction, data presentation, and conclusion drawing. The results show that the Sumbanese conceptualisation of the existence of Marapu and Nuku Zara is always placed in the realm of the existence of the divine creating the universe and the life of all creatures. The role of Nuku Zara in the Social and Religious Structure plays a central role as a divine entity that is the main purpose of all forms of respect and rituals. The symbolism in the Pangadi Nga'a Pabenudi We'e Marapu Ritual is Betel nut and areca nut in Sumba culture symbolise the unity of communication between humans and ancestral spirits and the Gods, in addition, rice and water symbolise life and fertility. The shift in meaning in the contemporary context due to the pressure of advancing modernisation causes most of the local wisdom with noble values in it to be increasingly degraded and eroded in meaning and the lack of awareness of the younger generation to maintain and preserve local wisdom.